Advancements and challenges in CAR-T cell therapy for solid tumors: A comprehensive review of antigen targets, strategies, and future directions - Jiajun Zhu; Jianming Zhou; Yiting Tang; Ruotong Huang; Chengjia Lu; Ke Qian; Qingyu Zhou; Jingjun Zhang; Xiaoyi Yang; Wenhan Zhou; Jiaqiang Wu; Qiudan Chen; et al. (Cancer Cell International)
Abstract Chimeric antigen receptor-modified T cell therapy, originally employed in hematological malignancies treatment, has made significant strides in addressing solid tumors in recent years. Presently, second-generation CAR-T therapy has reached clinical implementation, while fifth-generation CAR-T therapy is in active development. However, initial clinical trials in solid tumors have shown limited success, primarily due to the immunosuppressive microenvironment of the tumor and the scarcity of tumor-specific antigens. Nevertheless, emerging strategies, including combination therapies and gene editing technologies, exhibit promising potential in enhancing CAR-T cell effectiveness. In this review, we comprehensively examine the current state of research on CAR-T cell therapy for solid tumors, with a particular focus on the various antigenic targets that have been explored for solid tumors. We critically review established and novel targets, providing insights into their therapeutic potential and limitations. Additionally, we highlight the key challenges that currently hinder the success of CAR-T therapy in solid tumors, including the choice of target antigens, physical barriers, antigen escape, immunosuppressive microenvironment, and adverse reactions. Despite the formidable challenges confronting CAR-T cell therapy in solid tumors, ongoing research is forging a path towards its integration into the mainstream cancer treatment paradigm, offering renewed optimism for enhanced outcomes in patients afflicted with solid malignancies.